Propionibacterium acnes in the Pathogenesis and Immunotherapy of Acne Vulgaris - Liu, Pei-Feng; Hsieh, Yao-Dung; Lin, Ya-Ching; Two, Aimee; Shu, Chih-Wen; Huang, Chun-Ming (Current Drug Metabolism, 2015)
Acne vulgaris, a multi-factorial disease, is one of the most common skin diseases, affecting an estimated 80% of Americans at some point during their lives. The gram-positive and anaerobic Propionibacterium acnes (P. acnes) bacterium has been implicated in acne inflammation and pathogenesis. Therapies for acne vulgaris using antibiotics generally lack bacterial specificity, promote the generation of antibiotic-resistant bacterial strains, and cause adverse effects. Immunotherapy against P. acnes or its antigens (sialidase and CAMP factor) has been demonstrated to be effective in mice, attenuating P. acnes-induced inflammation; thus, this method may be applied to develop a potential vaccine targeting P. acnes for acne vulgaris treatment. This review summarizes reports describing the role of P. acnes in the pathogenesis of acne and various immunotherapy-based approaches targeting P. acnes, suggesting the potential effectiveness of immunotherapy for acne vulgaris as well as P. acnes-associated diseases.
Keywords: Acne vulgaris